rTMS investigation of resistant Obsessive-Compulsive Related Disorders: Efficacy of targeting the reward system - Di Ponzio, Michele; Makris, Nikos; Tenerini, Carlotta; Grassi, Eleonora; Ragone, Samuele; Pallanti, Stefano (Frontiers in Psychiatry, 2023)
Repetitive Transcranial Magnetic Stimulation (rTMS) is not only a therapeutic option but also an investigational tool to explore circuits and subjective dimensions in pathological conditions. In this explanatory study, rTMS has been used in patients with Obsessive-Compulsive Related Disorders (OCRD). Patients with trichotillomania, hoarding disorder and skin picking disorder were treated with rTMS over the left DLPFC at 15Hz, targeting the reward system via the connection with the nucleus accumbens and the ventral tegmental area. All patients were administered with SDQ and, depending on the condition, with HRS, MGH or NE-YBOCS at the baseline, at the end of the treatment and a 1-month follow-up. Analysis of the results showed a reduction in symptom severity at the end of the treatment in all three groups (p<0.0001) as well as a reduction in depression symptoms (p<0.01). Improvements at 1-month follow-up were maintained only in younger patients. Indeed, when changes in scores at the follow-up were analyzed separately for younger (<30 years) and older patients (>60 years), the elderly showed again an increase in symptoms severity, suggesting that the stability of TMS effects over time reduces with age, possibly as an effect of age-related reduction in brain plasticity. This study adopted with promising results a protocol (15Hz over the left DLPFC) targeting the reward system, typically employed in addictions. These results can be in line with the view of OCRD as behavioural addictions, suggesting the implication of common circuits, such as the reward system, in the mechanisms at the basis of these disorders.